Agriculture Risk Components for Rice Cultivation in Cigombong and Cibago - Wicaksono, Panji; Wiryono, Sudarso Kaderi (Journal of Business and Management, 2013)
Rice cultivation has a lot of risks associated with it. Hardaker et. Al (2004) says that there are five main dimensions in any agricultural activities: production risk, finance risk, market risk, technological risk, and institutional risk. These five risks are the main reference in this research. The research focuses on Cigombong and Cibago which are located near Bogor and Subang respectively. The focus in this research is to find risk components that are essential in rice cultivation in both Cigombong and Cibago. Also, this research tries to analyze the difference in the place of cultivation has on the agriculture risk. The research will depend on exploratory research methodologies such as literature review, interviews, and focus group discussion as well as using descriptive research methodologies in the form of questionnaires. The data that has been gathered will be analyzed using two statistical tools the Principal Component Analysis (PCA) and the Discriminant Analysis (DA). PCA will be used to identify the essential risks, while DA will be used to discriminate. The result that was found in both Cigombong and Cibago that production risk is the most significant risk according to the respondents. While marketing and financial risk are at the bottom two. Statistically, all of the data gathered are valid and reliable. While through the PCA it was found that there are 12 components that could be considered essential. These components represent 76.455% of the whole risk variables associated in agriculture risks. Furthermore, it was found that the DA statistically proves that the place where cultivation activities are done has an affect upon the overall agricultural risk.Ã‚Â Keywords: agricultural risk, risk components, variables